Financial Performance and Firm Value of Aviation Sector - Desiana Rachmawati; Zenita Kurniasari (Enrichment : Journal of Management, 2022)
This study aims to determine the financial performance based on the liquidity, solvency and profitability ratios and the effect on firm value. This research is a quantitative study using secondary data in the form of financial reports. The sample used is the airline sub-industry listed on the IDX, which publishes financial reports and annual reports for the 2017-2020 period. The analysis was carried out using multiple linear regression. Based on hipothesis test results, the liquidity ratio does not affect firm value. While the solvency ratio and the profitability ratio partially affect the firm value. Companies need to manage debt so that it is not too large and poses a solvency risk. Then, companies need to increase ancillary revenue in order to increase profit, so that profitability increases and will have an impact on increasing company value.